2020
DOI: 10.1007/s00210-020-01886-2
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal insufficiency is a contraindication for omalizumab therapy in mast cell activation disease: risk for serum sickness

Abstract: Omalizumab is an effective therapeutic humanized murine IgE antibody in many cases of primary systemic mast cell activation disease (MCAD). The present study should enable the clinician to recognize when treatment of MCAD with omalizumab is contraindicated because of the potential risk of severe serum sickness and to report our successful therapeutic strategy for such adverse event (AE). Our clinical observations, a review of the literature including the event reports in the FDA AE Reporting System, the Europe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…These immune complexes can deposit in various tissues, potentially causing inflammation and tissue damage, especially in organs such as the kidneys, and induce serum sickness, a delayed hypersensitivity reaction. 2,3 For patients with high tIgE, we regularly performed IgE immunoapheresis introductory to omalizumab treatment until September 2019. 4,5 However, postmarketing observational studies suggested that omalizumab efficacy is conserved also in asthmatic patients with tIgE >1500 UI/L without any significant side effect.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These immune complexes can deposit in various tissues, potentially causing inflammation and tissue damage, especially in organs such as the kidneys, and induce serum sickness, a delayed hypersensitivity reaction. 2,3 For patients with high tIgE, we regularly performed IgE immunoapheresis introductory to omalizumab treatment until September 2019. 4,5 However, postmarketing observational studies suggested that omalizumab efficacy is conserved also in asthmatic patients with tIgE >1500 UI/L without any significant side effect.…”
mentioning
confidence: 99%
“…One area of concern when using omalizumab is its potential impact on circulating immune complexes and renal function. 2,3 Serum sickness has been reported following treatment with omalizumab in the context of mast cell activation disease (MCAD). 3 Studies evaluating renal function in patients receiving omalizumab with initial tIgE<1500 kUI/L shown no significant effects on renal parameters, including serum creatinine levels and glomerular filtration rate.…”
mentioning
confidence: 99%
See 1 more Smart Citation